Analisis Siswa Adhd Di SDN Rancagong 2 - Nurfadhillah, Septy; Astuti, Indri Maya; Maemunah, Siti; Insyirah, Aniq; Rahma, Salsa Bila; Putri, Nadila Anggraeni; Anzani, Rahmah Wati; Lestari, Putri Indah (Lembaga Yasin AlSys, 2021)
This study aims to analyze ADHD students at SDN RANCAGONG 2 to find out what ADHD is, what are the strengths and weaknesses of ADHD children, and how to handle them in learning. This research method is observation with a descriptive approach that is explaining the problems in the field. This data collection technique is observation, interview and document study. This population sample uses all grades 1 and II and gets 1 child in grade 1 and 2 children in grade II. The result of this research is that students with special needs in grades I and II are students with difficulty concentrating and being hyperactive while studying. This can be seen during the learning process, students can only run here and there, talk continuously, to disturb others. For adhd children in school, we must know that the way to deal with adhd children is not by scolding them in class but the teacher's role in dealing with adhd children who feel in public schools in one way, namely making the teacher a playmate for children the adhd.